Desidratação de resíduos do processamento de maracujá-amarelo por diferentes metodologias - Silva, Neiton Carlos da (2015)
Brazil is one of the greatest producers of fruits in the world which involves the generation of a large amount of agro-industrial residues whose potential still needs to be better studied. The yellow passion fruit (Passiflora edulis f. flavicarpa) is rich in minerals, vitamins and fibers and its production generates a large number of by-products as peels and seeds, which can reach 70% of the fruit weight. Within this reality, the methods of dehydration stand out as an alternative to remove moisture of this material, preventing the proliferation of microorganisms and creating opportunities for its reutilization. In this work, it was studied the impact of four techniques of dehydration in the passion fruit s residue: hot air, infrared, microwaves and freeze drying. In all was possible to obtain a material with satisfactory final moisture levels, highlighting the use of microwaves as the most efficient in terms of time. Dehydration by hot air was positively affected by velocity and temperature conditions, but the bioactive compounds had impact of temperature and time (80oC and 7 hours). The temperature of 95oC was the most efficient for the moisture removal and contends of bioactive compounds in the dehydration of infrared, but an overexposure to this radiation beyond the observed limits must be avoided. The use of microwaves show that is possible to obtain a material with good final quality and quickly, since intermediate levels of powers (480 W) are used to avoid over exposure. Freezer drying produced a final product with better visual appearance but its great operation times and the final content of bioactive compounds found wasn t better to other methods, in exception of pectin contents. Analyzing the bioactive compounds, phenolics and flavonoids were positively impacted by dehydration, reach values near and above of the residue in natura in all techniques. Citric acid showed deterioration in all conditions observed, indicating its sensibility to thermal processes as much as freeze drying. The ascorbic acid was strongly influenced by heat exposure an increased its levels, except in the freeze drying samples. Overall, the best dehydration methodology was the microwave technique, indicating a potential future use of this method in the use of passion fruit residues.